Enoyl-Acyl Carrier Protein Reductase (INHA): A Remarkable Target to Exterminate Tuberculosis - Jain, Surabhi; Sharma, Smriti; Sen, Dhrubo J.; Pandya, Saurabh S. (Anti-Infective Agents, 2021)
Tuberculosis is an epidemic requiring new molecules with high potency and minimum side effects for its treatment. In the same respect, this review emphasises on important target enoyl-acyl carrier protein reductase or INHA crucial in the completion of the FAS II cycle. INHA has retained its fame since the inception of the drug Isoniazid, as inhibitors have a long residence time hence good activity. One of the causes of the failure of conventional drugs is resistance towards activating or target genes. Here, we propose direct inhibitors that do not need prior activation by Kat G. Some of the categories are Aryl amide, Piperazine, Thiadiazole, Benzamide, etc., that are specifically active against INHA, along with their structure-activity relationship. Many of them are efficient in micromolar concentration, whereas Pyrazole carboxamide is active in nanomolar concentration and derivative of 4-hydroxy pyridones was effective in vivo. Natural products are also in the way to combat tuberculosis. Furthermore, from available proteins of wild and mutant strains, new leads can be designed successfully by utilizing information of co-crystallized ligands.
Keywords: KAT G